Dual attentional processing of task-irrelevant information - Tsukasa Kimura; Tomoya Kawashima (Acta Psychologica)
Previous studies have demonstrated that repeated and regular presentations of task-irrelevant environmental stimuli enhance temporal prediction of subsequent events. However, the specific influence of such information processing at both the stimulus and contextual levels on temporal prediction remains unclear. This study aimed to elucidate the cognitive processing of task-irrelevant information by investigating how a stimulus that deviates from a sequence of repeated task-irrelevant stimuli is processed. To achieve this, we repeatedly presented three task-irrelevant stimuli before a discrimination task, manipulating whether the second stimulus' color deviated, and examined ERPs elicited by the target in the discrimination task as well as by task-irrelevant and deviant stimuli. In fixed and standard trials without deviations, CNV amplitudes for task-irrelevant stimuli increased just before the target stimulus, while P3a was absent. In deviant trials, CNV amplitude remained unchanged, whereas P3a amplitudes elicited by deviant and post-deviant stimuli increased compared to fixed and standard trials. Reaction times were shortest in fixed trials, followed by standard and deviant trials. These findings suggest that task-irrelevant information is processed through dual mechanisms: a stimulus-level process that responds to changes in task-irrelevant stimuli and a contextual-level process that regulates the allocation of attentional resources to such stimuli.